PENGARUH BRAND AMBASSADOR HEARTS2HEARTS DAN KOMUNIKASI PERSUASIF BEAUTY ADVISOR TERHADAP KEPUTUSAN PEMBELIAN - Nelly Nelly; Mardhiyah Dwi Ilhami (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to analyze the influence of Hearts2Hearts Brand Ambassadors and Beauty Advisor Persuasive Communication on Barenbliss Cosmetics Purchase Decisions among Faculty of Economics and Business, Muhammadiyah University of Bengkulu. The research method used was quantitative with a multiple linear regression approach. Data were collected through questionnaires distributed to 141 respondents, who were Barenbliss Cosmetics consumers and undergraduate students from the 2022-2024 intake at Faculty of Economics and Business, Muhammadiyah University of Bengkulu. The results showed a positive and significant influence of Hearts2Hearts Brand Ambassadors on Purchase Decisions, indicating that the stronger the Brand Ambassador's role, the higher the consumer's purchase decision. Furthermore, Beauty Advisor Persuasive Communication also positively influenced Purchase Decisions, indicating that the better the communication from the Beauty Advisor, the higher the consumer's purchase decision. Simultaneously, the Hearts2Hearts Brand Ambassadorand Beauty Advisor Persuasive Communication jointly influenced Purchase Decisions, with a significance value of F-value of 0.000 < 0.05. The results of this study conclude that Hearts2Hearts Brand Ambassadorand Beauty Advisor Persuasive Communication have a partial and simultaneous influence on Purchase Decisions among FEB students at Barenbliss Muhammadiyah University of Bengkulu. Keywords: Hearts2Hearts Brand Ambassador, Persuasive Communication, Beauty Advisor, Purchase Decision, Barenbliss